Differences in street-scale built environment preferences towards biking: a latent class analysis of stated choice data. Issue 3 (2nd September 2021) - Liu, Yanan; Yang, Dujuan; Timmermans, Harry J.P.; de Vries, Bauke
ABSTRACT: Biking contributes to a better environment by reducing short car trips and improving public health. The street-scale built environment affects the appeal of streets to cyclists, and thus influences route choice behaviour. This study develops a stated choice experiment that systematically varies eight attributes of the built environment to examine preference structure differences pertaining to the street-scale built environment among cyclists in the context of access/egress trip to a metro station. The environment is systematically varied in terms of road length, average number of building floors, retail frontage, cycling facilities at intersections, bike lane width, greenery, lamp density, and crowdedness. Eight hundred and three respondents completed the choice task using face to face interviews in Tianjin, China. Results suggest the existence of two latent classes of cyclists that differ in their preference for the street-scale built environment.